Testing the Chromosomal Speciation Hypothesis for Humans and Chimpanzees - Zhang, Jianzhi; Wang, Xiaoxia; Podlaha, Ondrej

(untitled) (Genome Research, 2004)
Fixed differences of chromosomal rearrangements between isolated populations may promote speciation by preventing between-population gene flow upon secondary contact, either because hybrids suffer from lowered fitness or, more likely, because recombination is reduced in rearranged chromosomal regions. This chromosomal speciation hypothesis thus predicts more rapid genetic divergence on rearranged than on colinear chromosomes because the former are less porous to gene flow. A number of studies of fungi, plants, and animals, including limited genetic data of humans and chimpanzees, support the hypothesis. Here we reexamine the hypothesis for humans and chimpanzees with substantially more genomic data than were used previously. No difference is observed between rearranged and colinear chromosomes in the level of genomic DNA sequence divergence between species. The same is also true for protein sequences. When the gorilla is used as an outgroup, no acceleration in protein sequence evolution associated with chromosomal rearrangements is found. Furthermore, divergence in expression pattern between orthologous genes is not significantly different for rearranged and colinear chromosomes. These results, showing that chromosomal rearrangements did not affect the rate of genetic divergence between humans and chimpanzees, are expected if incipient species on the evolutionary lineages separating humans and chimpanzees did not hybridize.